1876 Alabama Code 883, ch. 3, § 4110 - (:unkn) unknown (General Publisher, 1873)
Prohibited the concealed carrying of any brass knuckles, slungshots, or “other weapon of like kind or description.” Punishable by a fine of $20-200 and imprisonment or term of hard labor not to exceed 6 months.
--
Keywords: CARRY - CONCEALED - NON-GUN ARMS